If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x = 10x + 14 Multiply x * x x2 = 10x + 14 Reorder the terms: x2 = 14 + 10x Solving x2 = 14 + 10x Solving for variable 'x'. Reorder the terms: -14 + -10x + x2 = 14 + 10x + -14 + -10x Reorder the terms: -14 + -10x + x2 = 14 + -14 + 10x + -10x Combine like terms: 14 + -14 = 0 -14 + -10x + x2 = 0 + 10x + -10x -14 + -10x + x2 = 10x + -10x Combine like terms: 10x + -10x = 0 -14 + -10x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '14' to each side of the equation. -14 + -10x + 14 + x2 = 0 + 14 Reorder the terms: -14 + 14 + -10x + x2 = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -10x + x2 = 0 + 14 -10x + x2 = 0 + 14 Combine like terms: 0 + 14 = 14 -10x + x2 = 14 The x term is -10x. Take half its coefficient (-5). Square it (25) and add it to both sides. Add '25' to each side of the equation. -10x + 25 + x2 = 14 + 25 Reorder the terms: 25 + -10x + x2 = 14 + 25 Combine like terms: 14 + 25 = 39 25 + -10x + x2 = 39 Factor a perfect square on the left side: (x + -5)(x + -5) = 39 Calculate the square root of the right side: 6.244997998 Break this problem into two subproblems by setting (x + -5) equal to 6.244997998 and -6.244997998.Subproblem 1
x + -5 = 6.244997998 Simplifying x + -5 = 6.244997998 Reorder the terms: -5 + x = 6.244997998 Solving -5 + x = 6.244997998 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 6.244997998 + 5 Combine like terms: -5 + 5 = 0 0 + x = 6.244997998 + 5 x = 6.244997998 + 5 Combine like terms: 6.244997998 + 5 = 11.244997998 x = 11.244997998 Simplifying x = 11.244997998Subproblem 2
x + -5 = -6.244997998 Simplifying x + -5 = -6.244997998 Reorder the terms: -5 + x = -6.244997998 Solving -5 + x = -6.244997998 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = -6.244997998 + 5 Combine like terms: -5 + 5 = 0 0 + x = -6.244997998 + 5 x = -6.244997998 + 5 Combine like terms: -6.244997998 + 5 = -1.244997998 x = -1.244997998 Simplifying x = -1.244997998Solution
The solution to the problem is based on the solutions from the subproblems. x = {11.244997998, -1.244997998}
| 10c^3-22c^2+4c=2c | | 9x^2+13x=5x | | f/5--13=12 | | (x*x)+6x=2 | | 4m-m=15 | | 6x-1/x-3 | | (x+1)+(x-2)=3 | | 112.5= | | 20a^2-a-1=0 | | 5s-8=6 | | ln[2x]=0.66 | | 1.5/6=10?p | | Ln(2*x+3)=1.76 | | 2x-30=58 | | 3+n(4)=15 | | 7x-6+6x+2=180 | | 3x+11=33 | | 16x-2+11x-7=180 | | 16x-6+14x+6=180 | | 5x+1+5x-2=30 | | 20x+40x=180 | | 4x^4-12x^3+37x^2-42x+k=0 | | y+4=.5(x+4) | | 5x(x+3)+4=9-(x+1) | | y+9=-7(x+9) | | 5/6(9-6)y= | | U=6i-4j-23k | | 4x*4x+2x*2x=30 | | y=x^4-32x^2-144 | | y+5=-0.6(x+2) | | d/dx(x^11) | | (x*x)-11x=-28 |